Rehydration of Rosa rubiginosa Fruits Dried with Hot Air - Ohaco Dominguez, Elizabeth Haydee (2015)
The effect of perforation, drying temperature, and rehydration temperature on the rehydration kinetics of Rosa rubiginosa fruits was investigated. Before drying, half of the fruit sample was perforated three times at equidistant points along the equatorial plane of the fruit, in order to speed up the drying process. Samples were dried at various air temperatures (60, 70, and 80°C), with an air velocity of 5 m/s and 5% relative humidity. Then, dried samples were rehydrated at different temperatures (20, 40, 60, and 80°C). The rehydration kinetics was fitted by two empirical models, Peleg and Weibull, and both represented the phenomenon well, in perforated and nonperforated fruits. Regardless of the drying temperature, the higher the rehydration temperature of rose hip fruits, perforated or not, the higher the water absorption capacity. Temperature dependence of the kinetic parameters was Ea = 47.5 kJ/mol (Peleg) and 55.9 kJ/mol (Weibull) for nonperforated fruits and Ea = 40.1 kJ/mol (Peleg) and 45.5 kJ/mol (Weibull) for perforated fruits; thus, perforated fruits were influenced more by rehydration temperature than nonperforated fruits. Perforated fruits rehydrated 30% faster than nonperforated fruits.